Effects of CO2, Renewables and Fuel Prices on the Economic Growth in New Zealand - Duppati, Geeta; Tiwari , Aviral; Matlani, Neha (International Journal of Energy Economics and Policy, 2023)
This study investigates the impact of green policy initiatives on economic growth in the form of reduction in CO2 emissions, fossil fuel consumption, and an increase in renewable energy in New Zealand for the period 1980-2019. Our study addresses two questions: First, whether New Zealand managed to achieve economic growth while simultaneously decreasing emissions and increasing renewables? and second, whether the New Zealand GDP per capita is sensitive to the changes in fuel prices at the international level. Our study provides empirical insights on green policy initiatives, which will help refine early mitigation actions and support a transparent public debate about longer-term desirable and feasible mitigation pathways. We use a range of time series estimation techniques after the pre-diagnostic’s tests. The Johansen Cointegration test confirm long-term cointegration in the series. Our results from VECM suggests that the New Zealand economic growth and CO2 emissions are sensitive to the changes in the renewables, fossil fuels, brent and Australian coal prices in the long run. While our results from the error correction term indicate that renewables have the flexibility and potential to correct the short-run inconsistencies in economic growth at a significant speed and ensures equilibrium in the long run. But the brent and the Australian coal are likely to cause discrepancies in the short term and after which the error corrections in the long-term equilibrium are unlikely to happen. We also undertake impulse response function for forecasting the effects of economic growth, CO2 emissions, renewables, fossil fuels, brent and Australian coal on one another. Our results of economic growth on CO2 emissions, show differential short and long-run effects. In comparison, a negative CO2 emissions shock lasts for a brief period and triggers a very marginal short-term positive effect on economic growth and indicates that worsening or improving CO2 emissions will play an essential role in determining the level of economic growth in New Zealand. Therefore, it is crucial to execute policies that ensure a negative shock in CO2 emissions with long-term consequences on the economic growth with reduced emissions. Our study provides essential insights into the effectiveness of green initiatives on the economic growth of New Zealand.